2014
DOI: 10.1021/sb5002399
|View full text |Cite
|
Sign up to set email alerts
|

Speeding up Directed Evolution: Combining the Advantages of Solid-Phase Combinatorial Gene Synthesis with Statistically Guided Reduction of Screening Effort

Abstract: Efficient and economic methods in directed evolution at the protein, metabolic, and genome level are needed for biocatalyst development and the success of synthetic biology. In contrast to random strategies, semirational approaches such as saturation mutagenesis explore the sequence space in a focused manner. Although several combinatorial libraries based on saturation mutagenesis have been reported using solid-phase gene synthesis, direct comparison with traditional PCR-based methods is currently lacking. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 57 publications
3
46
0
2
Order By: Relevance
“…Parallel to these developments, solid‐phase gene synthesis emerged; this potentially offered a chemical alternative to the usual multistep molecular biological mutant library construction. Although an initial step in this direction was made by using the Sloning method for solid‐phase gene synthesis, it was not efficient enough to replace the traditional SM‐based approach, that is, fewer but still too many errors were found in the synthetic libraries. Unfortunately, in that report and in other directed‐evolution investigations, a systematic quality control at the DNA level based on massive sequencing was not made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel to these developments, solid‐phase gene synthesis emerged; this potentially offered a chemical alternative to the usual multistep molecular biological mutant library construction. Although an initial step in this direction was made by using the Sloning method for solid‐phase gene synthesis, it was not efficient enough to replace the traditional SM‐based approach, that is, fewer but still too many errors were found in the synthetic libraries. Unfortunately, in that report and in other directed‐evolution investigations, a systematic quality control at the DNA level based on massive sequencing was not made.…”
Section: Discussionmentioning
confidence: 99%
“…We have also reported the concept of combinatorial library construction based on assembly of designed oligonucleotides (ADO), but the library quality proved to be unsatisfactory at the DNA level . More recently, we compared a traditional PCR‐based SM‐library of P450‐BM3 mutants with the respective chemical library generated by solid‐phase synthesis by using the Sloning method . Although the quality of the Sloning library at the protein level proved to be somewhat higher, it was far from perfect, which suggested that the advantage of such a synthetic approach was limited.…”
Section: Introductionmentioning
confidence: 99%
“…A QuikChange experiment would be sufficient to generate 400 (20×20; two positions) or 8000 (three positions) different protein variants. Due to primer length limitations, saturation of more than three positions has to our best knowledge not been reported for the CASTing strategy 31,32,[76][77][78][79] . QuikChange based mutagenesis methods were further advanced to saturate 4 (PFunkel 80 ) to 6 (PFLF-MSDM 81 ) positions simultaneously.…”
Section: Comparison Of the Methods For Recombining Amino Acid Substitmentioning
confidence: 99%
“…These synthetic DNA libraries allow the sequence space of antibodies, enzymes, various other proteins, and genomes to be more thoroughly examined [69]. An example of the use of a DNA library in antibody research is the screen of a library of 10 10 variants for the humanization of antibodies [10].…”
Section: Introductionmentioning
confidence: 99%